Secondary battery and electric device

By blending NASICON type and garnet type solid electrolytes in the negative electrode sheet of liquid lithium-ion battery, the problems of poor solid-liquid interface wetting and insufficient safety of liquid lithium-ion battery are solved, and higher safety performance and Discharge performance.

CN119324196APending Publication Date: 2025-01-17NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310875902.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Liquid lithium-ion batteries are prone to fire and explosion in case of needle puncture due to poor wetting and poor safety of solid-liquid interfaces. The existing methods have not effectively improved these problems.

Method used

The NASICON type compound and garnet type compound are blended into the negative electrode active layer of the negative electrode sheet to act as solid electrolytes to optimize the current density distribution and safety performance and improve the needle puncture safety of lithium-ion batteries.

Benefits of technology

By blending specific solid electrolytes, the safety and discharge performance of liquid batteries are significantly improved, the solid-liquid interface wetting is improved, and the safety and ionic conductivity of lithium-ion batteries are enhanced. It is suitable for graphite and silicon-based negative electrode materials. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344733030000161
    Figure BDA0004344733030000161
  • Figure BDA0004344733030000171
    Figure BDA0004344733030000171
  • Figure HDA0004344733120000011
    Figure HDA0004344733120000011
Patent Text Reader

Abstract

The invention relates to a secondary battery and an electric device. The secondary battery comprises a positive pole piece, a negative pole piece and a diaphragm; the negative pole piece comprises a negative current collector and a negative active layer located on the surface of the negative current collector, the negative active layer comprises a negative active material and a solid electrolyte, and the solid electrolyte comprises an NASICON type compound and a garnet type compound. The electrode assembly can reduce the current caused by needling of the battery and improve the safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries can be divided into solid-state batteries and liquid-state batteries based on the electrolyte. Liquid batteries use electrolytes as the transfer medium for lithium ions, and the electrolyte forms a solid-liquid interface with the electrode. Solid-state batteries use solid electrolytes as the transfer medium for lithium ions, and the electrolyte forms a solid-solid interface with the electrode. The two are two types of lithium-ion batteries with significantly different electrochemical properties. For example, liquid batteries have poor solid-liquid interface wettability, poor thermal stability, and poor safety, such as fire and explosion during acupuncture. Solid-state batteries do not use liquid electrolytes, so they have better safety.

[0003] There is a method involving a negative electrode material, specifically mixing solid electrolyte and hard carbon into the negative electrode slurry of the liquid battery, thereby improving the uneven current density distribution and poor kinetic performance caused by the drastic change in the porosity of the pole piece and the uneven pore distribution after rolling of the traditional artificial graphite negative electrode. However, this method does not involve the improvement of the wettability of the liquid battery electrolyte and the safety of acupuncture. Summary of the invention

[0004] Based on this, the present invention provides a secondary battery and an electrical device with good acupuncture safety performance.

[0005] A first aspect of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator;

[0006] The negative electrode plate includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material and a solid electrolyte. The solid electrolyte includes a NASICON type compound and a garnet type compound.

[0007] In one embodiment, the NASICON-type compound comprises the general formula Li 1+x Al x Ti 2-x (PO 4 ) 3 At least one of the compounds shown, wherein 0 <x<0.5。

[0008] In one embodiment, the garnet-type compound comprises a general formula Li 7-b La 3 M 2-b O 12 At least one of the compounds shown, wherein M is selected from at least one of Zr, Ge, Mg and Al, and 0≤b≤1.

[0009] In one of the embodiments, the mass ratio of the NASICON type compound to the garnet type compound is 1:0.5 to 1:4.

[0010] In one embodiment, the Dv50 of the NASICON type compound and / or the garnet type compound is 200 nm to 3 μm.

[0011] In one embodiment, the mass percentage of the solid electrolyte in the negative electrode active layer is 0.5% to 2% by mass; and / or,

[0012] Calculated by mass percentage in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%.

[0013] In one embodiment, the negative electrode active material includes a silicon-based material;

[0014] Optionally, the silicon-based material includes at least one of a silicon-oxygen compound and a silicon-carbon compound;

[0015] Optionally, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 100%; further optionally, the mass percentage of the silicon-based material is 8% to 50%;

[0016] Optionally, based on the mass of the negative electrode active material, the negative electrode active material includes 0% to 92% of carbon-based material; further optionally, the mass percentage of the carbon-based material is 50% to 92%.

[0017] In one embodiment, the negative electrode active layer further comprises one or more of the following (a) to (c):

[0018] (a) 0.01% to 10% of a conductive agent, measured by mass percentage in the negative electrode active layer; optionally, the conductive agent comprises at least one of carbon black, graphite, carbon nanotubes, carbon fibers and graphene;

[0019] (b) 1% to 5% of a binder by mass in the negative electrode active layer; optionally, the binder comprises at least one of styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate and polyethylene acrylic acid;

[0020] (c) 0.5% to 1% by mass of a thickener in the negative electrode active layer; optionally, the thickener comprises at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0021] In one embodiment, the compaction density of the negative electrode active layer is 1.2 g / cm 3 ~2g / cm3 and / or,

[0022] The single surface density of the negative electrode active layer is 6 mg / cm 2 ~15mg / cm 2 .

[0023] A second aspect of the present application provides an electrical device powered by the secondary battery described in the first aspect.

[0024] The secondary battery mentioned above reduces the recognizability of the current caused by the battery being punctured by a needle, thereby improving the safety of the battery, by mixing a specific solid electrolyte, specifically a NASICON type compound and a garnet type compound, into the negative electrode.

[0025] In addition, by mixing specific solid electrolytes, the problem of poor wettability of the solid-liquid interface in liquid batteries can be effectively improved, and there is no need to mix additional additives such as hard carbon in the negative electrode, which has little impact on the main negative electrode material and can achieve good ion conductivity. At the same time, it is suitable for mixing traditional graphite negative electrode active materials and silicon-containing negative electrode active materials, achieving good negative electrode applicability. It also has good discharge performance and high discharge capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope (SEM) image of the negative electrode sheet prepared in Example 1. DETAILED DESCRIPTION

[0027] The secondary battery and the electric device of the present invention are further described in detail below in conjunction with specific embodiments. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0029] The optional scope of the terms "and / or" and "or / and" used in this article includes any one of two or more related listed items, and also includes any and all combinations of the related listed items, wherein any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items.

[0030] In this article, technical features described in an open manner (such as "including..." or "comprising...") include both closed technical solutions composed of the listed features and open technical solutions containing the listed features.

[0031] As used herein, a list of items connected by “at least one of,” “at least one of,” “at least one of,” or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase “at least one of A and B” means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase “at least one of A, B, and C” means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.

[0032] In this document, "first aspect", "second aspect", "third aspect", "fourth aspect", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0033] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0034] The percentage contents mentioned in this article, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0035] The percentage concentrations mentioned in this article, unless otherwise specified, refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0036] The temperature parameters involved in this article, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0037] A first aspect of the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator;

[0038] The negative electrode plate includes a negative current collector and a negative active layer on the surface of the negative current collector. The negative active layer includes a negative active material and a solid electrolyte. The solid electrolyte includes a NASICON-type compound and a garnet-type compound.

[0039] Understandably, the NASICON-type compound refers to a compound with the general formula Li 1+x A x B 2-x (PO 4 ) 3 , where A is selected from at least one of Ti, Zr, and Ge, B is selected from at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y, and La, and 0 < x ≤ 2.

[0040] Understandably, the garnet-type compound refers to a compound with the general formula Li w C i M 2-j Re 3-m O n , where C is selected from at least one of B, Al, Ga, In, Zn, Cd, Y, Sc, Mg, Ca, Sr, and Ba, M is selected from at least one of Zr, Hf, Nb, Ta, Mo, W, Sn, Ge, Si, Sb, Se, and Te, Re is selected from at least one of lanthanide elements and actinide elements, 5 ≤ w ≤ 7.5, 0 ≤ i ≤ 2, 0 ≤ j ≤ 2, 0 ≤ m ≤ 0.75, and 10.875 ≤ n ≤ 13.125.

[0041] Furthermore, by using specific types of NASICON-type compounds and garnet-type compounds and reasonably matching the two, the safety performance of the secondary battery can be optimized.

[0042] In one example, the NASICON-type compound includes at least one of the compounds represented by the general formula Li 1+x Al x Ti 2-x (PO 4 ) 3 , where 0 < x < 0.5. Further, the value of x includes, but is not limited to: 0.1, 0.2, 0.3, 0.4, 0.5. Furthermore, the NASICON-type compound is Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 .

[0043] In one example, the Dv50 of the NASICON type compound is 200nm to 3μm. Specifically, the Dv50 of the NASICON type compound includes but is not limited to: 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 700nm, 800nm, 900nm, 950nm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm.

[0044] In one example, the garnet-type compound includes a general formula Li 7-b La 3 M 2-b O 12 At least one of the compounds shown, wherein M is selected from at least one of Zr, Ge, Mg and Al, and 0≤b≤1. Examples include: Li 6.5 La 3 Al 1.5 O 12 , Li 7 La 3 Zr 2 O 12 Further, the value of b includes but is not limited to: 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1. Furthermore, the garnet-type compound is Li 7 La 3 Zr 2 O 12 .Li 7 La 3 Zr 2 O 12 It is a lithium-ion fast ion conductor with electrochemical stability. Under low potential conditions, it will not undergo reduction reaction and will not undergo related chemical reactions with the negative electrode material itself or the substances on the surface of the negative electrode material.

[0045] In one example, the Dv50 of the garnet-type compound is 200 nm to 3 μm. Specifically, the Dv50 of the garnet-type compound includes but is not limited to: 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 700 nm, 800 nm, 900 nm, 950 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm.

[0046] In one example, the mass ratio of the NASICON-type compound to the garnet-type compound is 1:0.5 to 1:4. Specifically, the mass ratio of the NASICON-type compound to the garnet-type compound includes, but is not limited to: 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5, 1:2.7, 1:3, 1:3.2, 1:3.5, 1:3.7, 1:4.

[0047] In one example, based on the mass percentage in the negative electrode active layer, the mass percentage of the solid electrolyte is 0.5% to 2%. Specifically, based on the mass percentage in the negative electrode active layer, the mass percentage of the solid electrolyte includes, but is not limited to: 0.2%, 0.5%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 4%, 5%.

[0048] In one example, based on the mass percentage in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%. Specifically, based on the mass percentage in the negative electrode active layer, the mass percentage of the negative electrode active material includes, but is not limited to: 90%, 91%, 92%, 93%, 94%, 95%, 96%.

[0049] In one example, the negative electrode active material includes a silicon-based material. The above-described solution of disposing the solid electrolyte in the negative electrode active layer is particularly applicable to silicon-containing negative electrodes, improving the fast charging performance of silicon-containing negative electrodes. Without limitation, the silicon-based material includes at least one of silicon, silicon alloy, silicon oxide compound, and silicon carbide compound. Specifically, examples of the silicon oxide compound include SiOx, nano-SiOx, etc. (0.5 < x < 1.5); examples of the silicon carbide compound include SiCx, etc. (0.5 < x < 1.5). In the present application, SiOx (0.5 < x < 1.5) refers to the average composition general formula of the silicon oxide compound, which may be a mixture, but as long as the average composition conforms to the above general formula. In the present application, SiCx (0.5 < x < 1.5) refers to the average composition general formula of the silicon carbide compound, which may be a mixture, but as long as the average composition conforms to the above general formula.

[0050] In one example, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 100%. Specifically, the mass percentage of the silicon-based material includes but is not limited to: 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%. Further, the mass percentage of the silicon-based material is 8% to 50%.

[0051] In one example, based on the mass of the negative electrode active material, the negative electrode active material includes 0% to 92% of carbon-based materials. Specifically, the mass percentage of the carbon-based material includes, but is not limited to: 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%. Further, the mass percentage of the carbon-based material is 50% to 92%. Without limitation, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, and the graphite may specifically be artificial graphite and / or natural graphite.

[0052] It is understandable that the negative electrode active layer may or may not include additives. Specifically, the additives are selected from at least one of a conductive agent, a binder, and a thickener.

[0053] In one example, the negative electrode active layer further includes 0.01% to 10% of a conductive agent, measured by mass percentage in the negative electrode active layer. Specifically, the mass percentage of the conductive agent includes, but is not limited to, 0.1%, 0.2%, 0.5%, 0.7%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, 7%, 9%, 10%. Without limitation, the conductive agent includes at least one of conductive carbon black, conductive graphite, carbon nanotubes (CNTs), carbon fiber (VGCF) and graphene. Among them, conductive carbon black can be exemplified by acetylene black, Super P, 350G, Ketjen black, etc.; conductive graphite can be exemplified by KS-6, etc.

[0054] In one example, the negative electrode active layer further comprises 0.2% to 5% of a binder by mass percentage in the negative electrode active layer. Specifically, the mass percentage of the binder includes, but is not limited to, 0.2%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, and 5%. Without limitation, the binder comprises at least one of styrene-butadiene rubber, polyacrylic acid (PAA), lithium polyacrylate, and polyethylene acrylic acid (PEAA).

[0055] In one example, the negative electrode active layer further comprises 0.2% to 5% of a thickener, measured by mass percentage in the negative electrode active layer. Specifically, the mass percentage of the thickener includes, but is not limited to, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 2%, 2.5%, 3%, 4%, and 5%. Without limitation, the thickener comprises one or both of sodium carboxymethyl cellulose (CMC-Na) and lithium carboxymethyl cellulose (CMC-Li).

[0056] In one example, the negative electrode active layer does not contain other admixtures, such as soft carbon, hard carbon, etc.

[0057] In one example, the compaction density of the negative electrode active layer is 1.2 g / cm 3 ~2g / cm 3 , for example 1.2 g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 .

[0058] In one example, the single-surface density of the negative electrode active layer is 6 mg / cm 2 ~15mg / cm 2 , for example 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 .

[0059] In one example, the negative electrode current collector is copper foil, stainless steel foil, graphite foil, graphite sheet or carbon cloth.

[0060] In one example, the total thickness of the negative electrode (including the negative electrode current collector and the negative electrode active layer) is 110 μm to 150 μm.

[0061] In addition, there is no particular limitation on the positive electrode sheet in the secondary battery. In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on the surface of the positive electrode current collector, and the positive electrode active layer includes a positive electrode active material. Further, the positive electrode active material is not limited and can be lithium iron phosphate (LiFePO 4 ) and other olivine structure lithium metal oxides, layered lithium metal oxides, spinel structure lithium metal oxides, etc.

[0062] Wherein, the layered lithium metal oxide can be selected from lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), ternary material LiNi x Co y Mn z O 2 (wherein 0≤x,y,z≤1, x+y+z=1) and their combinations.

[0063] It is understandable that the positive electrode active layer may or may not include additives. Specifically, the additives are selected from at least one of a conductive agent, a binder, and a thickener.

[0064] In one example, the positive electrode current collector is glassy carbon, graphite foil, graphite sheet, carbon cloth, carbon felt, carbon fiber, Ni, Al, Fe, Cu, the above metals after passivation treatment, stainless steel, carbon steel, Al alloy, Ni alloy, Ti alloy or the above alloys after passivation treatment.

[0065] There is no particular limitation on the separator in the secondary battery, and its function is to separate the positive electrode from the negative electrode. The separator can be made of polyethylene separator, polypropylene separator or glass fiber separator.

[0066] It is understandable that the secondary battery further comprises an electrolyte. The electrolyte is not particularly limited. In one example, the electrolyte comprises a lithium salt. Further, the lithium salt comprises LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 and LiN(CF 3 SO 2 ) 2 Furthermore, the concentration of the lithium salt in the electrolyte is 0.8M to 1.5M.

[0067] In one example, the secondary battery is a lithium-ion battery. Without limitation, the lithium-ion battery can be a soft-pack battery, a square-shell battery, or a cylindrical battery cell.

[0068] In one example, the cell capacity of the secondary battery is 10Ah to 100Ah.

[0069] In one example, the secondary battery can be punctured to a depth greater than 4 mm by a step needle, and further, the secondary battery can be punctured to a depth greater than 5 mm by a step needle.

[0070] The present invention also provides an electrical device powered by the secondary battery. Without limitation, the electrical device may be consumer electronics or electric vehicles.

[0071] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0072] Example 1

[0073] This embodiment provides a lithium ion battery, and the manufacturing method thereof is as follows:

[0074] (1) Production of negative electrode sheet:

[0075] 1.1 Preparation of negative electrode slurry: negative electrode active material (60% graphite, 40% silicon oxide), conductive agent (Super-P), binder (styrene-butadiene rubber), thickener (sodium carboxymethyl cellulose), solid electrolyte 1 (NASICON type compound Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 powder, particle size Dv50 is 0.3 μm), solid electrolyte 2 (garnet compound Li 7 La 3 Zr 2 O 12 Powder, particle size Dv50 is 0.5 μm) according to the mass percentage of 94.5%: 0.7%: 3%: 0.8%: 0.5%: 0.5%, the obtained mixture is added with water according to the solid content of 45%, stirred evenly, and the negative electrode slurry is obtained;

[0076] 1.2 The negative electrode slurry of step 1.1 is coated on the negative electrode current collector copper foil, dried in a drying oven at 90°C, and then rolled and sliced ​​to obtain a negative electrode sheet; the compaction density of the negative electrode sheet is 1.6 g / cm 3 , single surface density (excluding foil) is 9 mg / cm 2 ;

[0077] (2) Production of positive electrode:

[0078] 2.1 Preparation of positive electrode slurry: The positive electrode active material (NMC), conductive agent (carbon black) and binder (PVDF) are mixed according to the mass percentage of 97.5%:1.5%:1%, and the obtained mixture is added with N-methyl-2-pyrrolidone (NMP) solvent according to the solid content of 50%, and stirred evenly to obtain positive electrode slurry;

[0079] 2.2 The positive electrode slurry of step 2.1 was coated on the positive electrode current collector aluminum foil, dried in a drying oven at 110°C, and then rolled and sliced ​​to obtain a positive electrode sheet; the compaction density of the positive electrode sheet was 3.6 g / cm 3 , single surface density is 23mg / cm 2 ;

[0080] (3) Lithium-ion battery assembly:

[0081] The separator (PE separator), negative electrode sheet, separator (PE separator), and positive electrode sheet are stacked and wound in the order and placed in an aluminum-plastic bag. After drying the water, the electrolyte (1 mol / L LiPF 6 A solution of lithium salt in a DMC / EC / EMC solvent with a mass ratio of 1:1:1) is prepared, and finally a lithium-ion battery is obtained after packaging, formation and constant volume.

[0082] The prepared lithium-ion battery has a cell capacity of 100Ah.

[0083] Example 2

[0084] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of Embodiment 1, except that the weight percentages of the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 and the solid electrolyte 2 are 94.5%:0.7%:3%:0.8%:0.3%:0.7%.

[0085] Example 3

[0086] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of Embodiment 1, except that the weight percentages of the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 and the solid electrolyte 2 are 94.5%: 0.7%: 3%: 0.8%: 0.25%: 0.75%.

[0087] Example 4

[0088] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of embodiment 1, the main difference is that: the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 (NASICON type compound Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3powder, particle size Dv50 is 0.2 μm), and solid electrolyte 2 (garnet compound Li 7 La 3 Zr 2 O 12 The weight percentages of powder (particle size Dv50 is 1 μm) are 94.5%: 0.7%: 3%: 0.8%: 0.3%: 0.7%.

[0089] Example 5

[0090] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of embodiment 1, the main difference is that: the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 (NASICON type compound Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 powder, particle size Dv50 is 0.2 μm), and solid electrolyte 2 (garnet compound Li 6.5 La 3 Mg 1.5 O 12 The weight percentages of powder (particle size Dv50 is 1 μm) are 94.5%: 0.7%: 3%: 0.8%: 0.3%: 0.7%.

[0091] Example 6

[0092] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of embodiment 1, the main difference is that: the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 (NASICON type compound Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 powder, particle size Dv50 is 0.2 μm), and solid electrolyte 2 (garnet compound Li 6.5 La 3 Al 1.5 O 12 The weight percentages of powder (particle size Dv50 is 1 μm) are 94.5%: 0.7%: 3%: 0.8%: 0.3%: 0.7%.

[0093] Example 7

[0094] This embodiment provides a lithium ion battery, and its manufacturing method is the same as that of embodiment 1, the main difference is that: the negative electrode active material, the conductive agent, the binder, the thickener, the solid electrolyte 1 (NASICON type compound Li 1.2 Al 0.2 Ti 1.8 (PO4 ) 3 powder, particle size Dv50 is 1 μm), and solid electrolyte 2 (garnet oxide Li 6.5 La 3 Al 1.5 O 12 The weight percentages of powder (particle size Dv50 is 1 μm) are 94.5%: 0.7%: 3%: 0.8%: 0.3%: 0.7%.

[0095] Comparative Example 1

[0096] This comparative example provides a lithium ion battery, and its manufacturing method is the same as that of Example 1, the main difference is that the solid electrolyte only uses NASICON type compound Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The powder has a particle size Dv50 of 0.3 μm. The weight percentages of the negative electrode active material, the conductive agent, the binder, the thickener, and the solid electrolyte are 94.5%: 0.7%: 3%: 0.8%: 1%.

[0097] Comparative Example 2

[0098] This comparative example provides a lithium ion battery, and its manufacturing method is the same as that of Example 1, the main difference is that: the solid electrolyte only uses a garnet compound Li 7 La 3 Zr 2 O 12 The powder has a particle size Dv50 of 0.5 μm. The weight percentages of the negative electrode active material, the conductive agent, the binder, the thickener, and the solid electrolyte are 94.5%: 0.7%: 3%: 0.8%: 1%.

[0099] Comparative Example 3

[0100] This comparative example provides a lithium ion battery, and its manufacturing method is the same as that of Example 1, the main difference is that: the solid electrolyte only uses a garnet compound Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 The powder has a particle size Dv50 of 0.4 μm. The weight percentages of the negative electrode active material, the conductive agent, the binder, the thickener, and the solid electrolyte are 94.5%: 0.7%: 3%: 0.8%: 1%.

[0101] Comparative Example 4

[0102] This comparative example provides a lithium ion battery, and its manufacturing method is the same as that of Example 1, the main difference being that it does not contain a solid electrolyte, and the weight percentages of the negative electrode active material, the conductive agent, the binder, and the thickener are 95.5%:0.7%:3%:0.8%.

[0103] Test example:

[0104] Take the lithium ion batteries (cells) of each embodiment and comparative example and test them according to the following method:

[0105] (1) DC internal resistance test: After the battery cell has completed the battery cell capacity calibration, use an internal resistance meter to test the internal resistance of the battery cell in a fully charged state. The steps for capacity calibration are as follows:

[0106] 1-1) 25±2℃, let stand for 5min;

[0107] 1-2) 25±2℃, charge to 4.25V with 1 / 3C CC-CV, and the cut-off current is 1 / 20C;

[0108] 1-3) 25±2℃, let stand for 30min;

[0109] 1-4) 25±2℃, discharge to 2.5V at 1 / 3C;

[0110] 1-5) 25±2℃, stand for 30min;

[0111] 1-6) Repeat steps 1-2) to 1-5), (the second week calibration discharge capacity is taken as C0);

[0112] 1-7) 25±2℃, charge to 4.25V with 1 / 3C0 CC-CV, the cut-off current is 1 / 20C0; 1-8) end;

[0113] (2) Rate test: 2-1) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, cut-off current is 1 / 20C; 2-2) 25±2℃, stand for 30min;

[0114] 2-3) 25±2℃, discharge to 2.5V at 1 / 2C;

[0115] 2-4) 25±2℃, let stand for 30min;

[0116] 2-5) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, cut-off current is 1 / 20C; 2-6) 25±2℃, stand for 30min;

[0117] 2-7) 25±2℃, discharge at 1C to 2.5V;

[0118] 2-8) 25±2℃, stand for 30min;

[0119] 2-9) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, cut-off current is 1 / 20C; 2-10) 25±2℃, stand for 30min;

[0120] 2-11) 25±2℃, discharge at 2C to 2.5V;

[0121] 2-12) 25±2℃, stand for 30min;

[0122] 2-13) 25±2℃, charge to 4.25V with 1 / 2C CC-CV, cut-off current is 1 / 20C; 2-14) 25±2℃, stand for 30min;

[0123] 2-15) 25±2℃, discharge at 3C to 2.5V;

[0124] 2-16)25±2℃, let stand for 30min.

[0125] (3) Step acupuncture:

[0126] The fully charged battery cell was subjected to a step-by-step puncture test. The specific test steps are as follows:

[0127] 3-1) Acupuncture location: center of the large surface of the battery cell;

[0128] 3-2) Needle diameter: 1mm;

[0129] 3-3) Needle tip angle: 30°;

[0130] 3-4) Needle puncture speed: 2 mm / s;

[0131] 3-5) Needle penetration depth: penetrate 1.25mm into the center of the large surface perpendicular to the battery direction, wait for 15s, if there is no loss of control, continue to step 1.25mm until the battery cell is penetrated.

[0132] (4) Wettability test:

[0133] Use a needle with a diameter of 1.0 mm to place a drop of electrolyte (1 mol / L LiPF 6 A solution of lithium salt in a DMC / EC / EMC solvent with a mass ratio of 1:1:1) is dropped on the surface of the negative electrode. The appearance image of the electrolyte is obtained through a microscope lens and a camera, and then the contact angle of the droplet in the image is calculated using digital image processing and some algorithms.

[0134] 5) Surface morphology of negative electrode sheet: The surface morphology of the negative electrode sheet prepared in Example 1 was observed by scanning electron microscopy (SEM). Figure 1 shown.

[0135] The test results are shown in Table 1 below:

[0136] Table 1

[0137]

[0138]

[0139] Note: Each battery cell is based on the 1 / 3C discharge capacity. The discharge current of different rates is adjusted to test the discharge capacity of the battery cell and the capacity retention rate is calculated.

[0140] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0141] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to interpret the contents of the claims.

Claims

1. A secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and separator; The negative electrode plate includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material and a solid electrolyte. The solid electrolyte includes a NASICON type compound and a garnet type compound.

2. The secondary battery according to claim 1, characterized in that: The NASICON type compounds include the general formula Li 1+ x Al x Ti 2-x At least one of the compounds represented by (PO4)3, wherein 0 <x<0.5。 3. The secondary battery according to claim 1, characterized in that: The garnet-type compound includes the general formula Li 7- b 3M 2-b O 12 At least one of the compounds shown, wherein M is selected from at least one of Zr, Ge, Mg and Al, and 0≤b≤1.

4. The secondary battery according to claim 1, characterized in that: The mass ratio of the NASICON type compound to the garnet type compound is 1:0.5 to 1:

4.

5. The secondary battery according to claim 1, characterized in that: The Dv50 of the NASICON type compound and / or the garnet type compound is 200nm to 3μm.

6. The secondary battery according to claim 1, characterized in that: The mass percentage of the solid electrolyte in the negative electrode active layer is 0.5% to 2%; and / or, Calculated by mass percentage in the negative electrode active layer, the mass percentage of the negative electrode active material is 90% to 96%.

7. The secondary battery according to claim 1, characterized in that: The secondary battery meets at least one of the following conditions: (a) the negative electrode active material comprises a silicon-based material; (b) the negative electrode active layer further comprises 0.01% to 10% of a conductive agent, based on the mass percentage in the negative electrode active layer; (c) the negative electrode active layer further comprises 1% to 5% of a binder, based on the mass percentage in the negative electrode active layer; (d) The negative electrode active layer further comprises 0.5% to 1% of a thickener, based on mass percentage in the negative electrode active layer.

8. The secondary battery according to claim 7, characterized in that: The silicon-based material comprises at least one of a silicon-oxygen compound and a silicon-carbon compound; and / or, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 8% to 50%; and / or, Based on the mass of the negative electrode active material, the negative electrode active material includes 50% to 92% of carbon-based material; and / or, The conductive agent includes at least one of carbon black, graphite, carbon nanotubes, carbon fibers and graphene; and / or, The binder comprises at least one of styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate and polyethylene acrylic acid; and / or, The thickener includes at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The compaction density of the negative electrode active layer is 1.2 g / cm 3 ~2g / cm 3 and / or, The single surface density of the negative electrode active layer is 6 mg / cm 2 ~15mg / cm 2 .

10. An electrical device, characterized in that: Power is supplied by the secondary battery according to any one of claims 1 to 9.